Transplantation and Adoptive Cellular Therapy of Cancer: The Role of T-Cell Growth Factors - Michael T. Lotze M.D. (Cell Transplantation, 1993)
The ability to transfer cultured lymphocytes required the availability and the understanding of the use of the T-cell growth factors IL-2, IL-4, IL-7, and IL-12. Application of these cytokines in vitro and in vivo has allowed the modern development of adoptive transfer of tumor reactive lymphocytes to the modern immunotherapy of patients with cancer. In a randomized prospective study of IL-2 administration compared with IL-2 and lymphokine-activated killer (LAK) cells, no increase in response rate was observed. In a total of 90 patients randomized to receive LAK and IL-2 and 91 patients randomized to receive IL-2 alone, there were a total of 24 responses in patients receiving cells and IL-2 and 16 responses in those receiving IL-2 alone (no significant difference). There was some suggestion that complete responses were observed more often in melanoma patients treated with LAK and IL-2. The most interesting aspect of this study is the prolonged duration of responses, lasting for many months or years. Unfortunately, given the large numbers of variables that were examined, it became very difficult to demonstrate a clear-cut association between clinical outcome (response) and any variable that was routinely measured. Significant antitumor responses have been observed greater than expected with IL-2 alone, with the administration of tumor-infiltrating lymphocytes to patients with melanoma. We currently use hollow fiber devices (Cellco, Germantown, MD) to expand cells up through the many doublings required to generate approximately 1-2 × 1011 cells over a period of 6 wk in culture. In a recent review of the results in patients with melanoma treated on such regimens in combination with high-dose IL-2, an approximately 20-50% response rate has been observed. The factors associated with response are still unclear. Although we initially felt that it was associated with specific lysis, subsequent studies from our group suggest that the relevant factor is specific cytokine (INF-γ, GM-CSF, TNF) production upon tumor stimulation. Additional studies will need to be done to clarify these issues.